Monetary policy normalisation and mortgage arrears in a recovering economy: The case of the Irish residential market - Rachel Slaymaker; Conor O'Toole; Kieran McQuinn; Mike Fahy (The Economic and Social Research Institute (ESRI), 2019)
In this paper we examine the sensitivity of mortgage arrears for Irish households to changes in mortgage interest rates under a series of plausible monetary policy normalisation scenarios. Using panel data over the period 2004 - 2016 we exploit information on current income and current mortgage repayments to link arrears to the level of, as well as shocks in, households' current debt service ratio. In doing so we address gaps in the existing literature on modelling default and stress testing. Both are found to be strong drivers of arrears indicating the level of indebtedness, as well as changes to repayment capacity, matter for households. We find that a 100 basis point increase in policy rates would lead to a 0.5 percentage point increase in new default flows. We also test for heterogeneous effects across households and find younger, low income households and those on tracker mortgage rate loans are most at risk following rate rises. This has important consequences for the distributional impacts of monetary policy.
Keywords: D14; E52; G21; R31; 330; Mortgage default; Credit Risk; Interest Rates; Debt Service Ratio